The Role of Rural Cooperatives in Marketing of Agricultural Products A Case Study of Fars Province - B Najafi; Z Farajzadeh (تعاون و کشاورزی, 2010)
The objective of this study was to shed light on the present role of rural cooperatives in marketing of agricultural products and their potential to expand such activities. The data were collected from a randomly selected sample of cooperative members (765) in rural cooperatives (17) of Fars province. The required information was collected through questionnaires which were filled by selected cooperative members of Shiraz, Darab, Eghlid, Kazeroun and Marvdasht in 2005. For more accurate investigation of member’s characteristics in tendency to participate in participating marketing and sales of products through cooperatives, diagnosis-analysis method was used. The results of study revealed that rural cooperatives were active, to some extent, in supplying inputs such as fertilizer and pesticides but did not participated in marketing of agricultural products. In spite of this, cooperative members had tendency to market their products through their cooperatives because of advantages such as higher prices and access to a fair marketing channel. The results of the study also indicated that most of cooperative members because of financial troubles are not able to store and market their products after harvest and because of vast amount of intermediate dealers, a considerable amount of harvest are pre-purchased before or after harvesting. The most important limitations that cooperative faces in marketing are lack of financial and physical facilities. In conclusion the article suggest solutions for these limitations.